Consolidating Erasmus Mobility in Spain during the Economic Crisis - Pérez Encinas, Adriana (International Higher Education, 2014)
This article explores how interest in the ERASMUS program has been consolidated in Spain at a time of severe economic crisis, when students see the opportunities it offers through study and internships abroad as a means to enhance their employability in a difficult job market.